Strengthening The PAI and Buddy Programs In Efforts To Prevent Bullying In The School Environment - Nahuda; Zulfitria; Uwes Sanusi (International Journal of Economics, Management, Business, and Social Science (IJEMBIS), 2026)
This study discusses the strengthening of Islamic Religious Education (PAI) and the implementation of the Buddy Program as an integrated strategy to prevent bullying in schools. The prevalence of bullying in various educational institutions demonstrates the need for interventions that are not only curative, but also preventive and sustainable. Strengthening PAI plays a crucial role in instilling noble moral values, empathy, caring, and social responsibility in students. Through a contextual, collaborative, and character-oriented learning approach, PAI becomes the foundation for building a religious, humanistic, and child-friendly school culture. This study used a qualitative approach with data collection techniques through observation, interviews, and documentation in schools implementing both programs. The results show that the integration of PAI and the Buddy Program is effective in reducing the potential for bullying behavior and fostering an inclusive and empathetic school climate. In conclusion, the synergy between values ​​education through PAI and social assistance through the Buddy Program serves as a strategic model that can be implemented in holistic and sustainable bullying prevention efforts